Some New Characterizations of Ruled Surfaces with B-Focal Curve According to Bishop Frame in E3 - Altay Suroglu, Gulden (Amer Inst Physics, 2018)
In this paper, we study some properties of ruled surfaces which are generated by B-focal curve according to Bishop frame in E-3. Then, we deduce in which conditions these ruled surfaces are minimal surface.
1ST INTERNATIONAL CONFERENCE ON MATHEMATICAL AND RELATED SCIENCES (ICMRS) -- APR 30-MAY 04, 2018 -- Antalya, TURKEY
Keywords: Constant-Angle Surfaces; Helix